平方: 9 K0 a g/ I- x( ^2 d' F
sin^2(α)+cos^2(α)=1 $ h ?! {. j8 ^" F4 ]& s
cos^2a=(1+cos2a)/2 ( M! `: |2 ^* d8 w! }4 D+ g
tan^2(α)+1=sec^2(α) : L. B( F" G3 G+ z$ |4 K
sin^2a=(1-cos2a)/2
, V4 ~! [1 h3 V, Ecot^2(α)+1=csc^2(α) * H) `( a' s- u! g. G
1 d; _2 M+ D+ q) B, R, Y
积:
$ P7 Z$ l0 [) M2 {; \$ W8 _" csinα=tanα*cosα
. }! Y4 G8 h/ J1 u4 a9 p: }. a3 ocosα=cotα*sinα * k9 V' E, n3 Q7 m5 a1 `! R2 }
tanα=sinα*secα
5 x% N0 T7 @* u9 G2 G! g8 v4 ^cotα=cosα*cscα , {' ^# x* l U/ }
secα=tanα*cscα
( a& C2 d2 n7 S; u* U$ f0 rcscα=secα*cotα
7 D2 k5 e3 M: d6 O& @. g; k6 C5 h4 [$ ^7 {
倒数: 8 g' n, S/ @+ V5 P
tanα·cotα=1 7 g! g% u' w2 ~9 h6 i: M
sinα·cscα=1 8 N* `" z& t6 u7 n4 z3 p
cosα·secα=1 3 j# p- F6 t5 n- m0 T0 w
$ p* B* T% u8 b# B% W三角函数恒等变形公式 6 R# b6 X' F9 v) n4 H' _: x$ O; [
. c x% t7 ~. k( s* e, ?9 B7 U
两角和差:
! K; D6 v" t- Z# \0 W H/ w0 Y* q( ccos(α+β)=cosα·cosβ-sinα·sinβ 7 A* @- S( k4 M$ `& @: m
cos(α-β)=cosα·cosβ+sinα·sinβ
5 @5 j# j! D$ y1 C5 N. g) {% Ksin(α±β)=sinα·cosβ±cosα·sinβ + d' e& }) x. C. `, A0 ~2 G9 P
tan(α+β)=(tanα+tanβ)/(1-tanα·tanβ) - a9 I/ E& k' R" o. m
tan(α-β)=(tanα-tanβ)/(1+tanα·tanβ)
3 i9 I% @. Q. H6 e' x
* ~0 j2 J3 |; [' s6 B3 S: z. |6 g三角和差: - i4 e0 |/ i+ d
sin(α+β+γ)=sinα·cosβ·cosγ+cosα·sinβ·cosγ+cosα·cosβ·sinγ-sinα·sinβ·sinγ
# |$ {4 ?) L: H' E9 }cos(α+β+γ)=cosα·cosβ·cosγ-cosα·sinβ·sinγ-sinα·cosβ·sinγ-sinα·sinβ·cosγ / D! {9 P/ r) U! X* n. J! _
tan(α+β+γ)=(tanα+tanβ+tanγ-tanα·tanβ·tanγ)/(1-tanα·tanβ-tanβ·tanγ-tanγ·tanα)
9 L4 J# B2 P# C6 Z0 h8 z# y6 F/ C, I- v$ O- C1 |( |
辅助角公式:
# B. Z9 q. E7 `, P3 T- z2 F% z9 pAsinα+Bcosα=(A^2+B^2)^(1/2)sin(α+t),其中
3 l0 w0 W- i4 j% ~sint=B/(A^2+B^2)^(1/2)
$ B: G' o i0 f( }$ y; Bcost=A/(A^2+B^2)^(1/2)
8 j g4 U: d! y# r+ S. ztant=B/A 8 D1 S0 G6 e$ v4 I
Asinα+Bcosα=(A^2+B^2)^(1/2)cos(α-t),tant=A/B : D/ E( l+ V! \. P! [8 e
6 d9 q% A5 H" b) Q, J2 d7 _6 Q
倍角公式: $ P3 Z# S, `8 x" T2 ~5 W" i, k. l
sin(2α)=2sinα·cosα=2/(tanα+cotα) ; w9 ^$ Q7 @% X+ _) ~- r
cos(2α)=cos^2(α)-sin^2(α)=2cos^2(α)-1=1-2sin^2(α) 0 j; t6 B4 o8 T5 Y, z1 Z
tan(2α)=2tanα/[1-tan^2(α)] ; G% ]7 P! h1 r6 t# ?# L. J! b" G
+ N* }1 I8 H( E0 d1 }
三倍角公式:
6 e6 Z. S* {9 xsin(3α)=3sinα-4sin^3(α) 0 _- q T; n+ d) O. J
cos(3α)=4cos^3(α)-3cosα 7 Q: P7 \+ l4 J# C" \" h. P
0 d/ r; J/ z* [
半角公式: 5 k+ V2 D) W* c
sin(α/2)=±√((1-cosα)/2)
) R5 w6 Y8 f2 E: Y' E8 x# ~8 |cos(α/2)=±√((1+cosα)/2)
8 U' e4 N8 e @7 u _tan(α/2)=±√((1-cosα)/(1+cosα))=sinα/(1+cosα)=(1-cosα)/sinα
5 V) T# m1 b! }. E0 Q, E+ M: g6 w8 V4 \/ a
降幂公式 ( g% ]4 U- i0 [3 k. ^! m0 p& O
sin^2(α)=(1-cos(2α))/2=versin(2α)/2
* m- b. U3 U) u3 Y3 x# Fcos^2(α)=(1+cos(2α))/2=covers(2α)/2 2 \3 A) L, V* F3 `9 @, b
tan^2(α)=(1-cos(2α))/(1+cos(2α)) 5 E {7 n3 A6 ^, b/ w% |" \
7 D5 @" K, J, o4 `7 J' `
万能公式:
/ {) Q& b( t1 a$ I' D d- Esinα=2tan(α/2)/[1+tan^2(α/2)]
+ u6 e/ S+ J; l. n) r$ E; Ncosα=[1-tan^2(α/2)]/[1+tan^2(α/2)]
* i+ @4 l% Q/ p+ c3 L6 A2 Jtanα=2tan(α/2)/[1-tan^2(α/2)] 3 c \# A/ m7 F1 d
; \: S! |# S# Z8 u u2 Z积化和差: 0 I' Y8 |* b/ x
sinα·cosβ=(1/2)[sin(α+β)+sin(α-β)]
% ~' g4 U1 t2 a) w5 X8 Icosα·sinβ=(1/2)[sin(α+β)-sin(α-β)]
' k6 [" G. L( k c V% [cosα·cosβ=(1/2)[cos(α+β)+cos(α-β)] 4 z: N% D% |3 {. l
sinα·sinβ=-(1/2)[cos(α+β)-cos(α-β)]
% k q4 Z5 s& _ T. D: N7 Z; _/ R1 B$ t/ `% T) C
和差化积: 1 O- ~5 J; v. J7 H7 W g# y( f* A/ `
sinα+sinβ=2sin[(α+β)/2]cos[(α-β)/2] / l, C5 u- e4 r+ c( {( Q0 T7 C* u
sinα-sinβ=2cos[(α+β)/2]sin[(α-β)/2]
3 f1 j& \) R. u* k, R1 j9 T1 K) n9 Hcosα+cosβ=2cos[(α+β)/2]cos[(α-β)/2]
I5 D1 _5 C b. scosα-cosβ=-2sin[(α+β)/2]sin[(α-β)/2] 8 c, {! B) O0 V0 u
2 ?% ~; K/ C# {& R4 q1 K
推导公式: 4 E- D, [8 N' m! C; ~, Q
tanα+cotα=2/sin2α
' J4 ?3 j! f) Y" _/ Z$ H7 ptanα-cotα=-2cot2α % e' o. r7 r% S9 H
1+cos2α=2cos^2α
6 q F2 g* K9 ?1 G1-cos2α=2sin^2α " r0 K4 O, l4 x o
1+sinα=(sinα/2+cosα/2)^2
* |5 e5 D# K2 y0 B5 O1 E- k; Q% G
其他:
3 U ~( H. s0 e9 s2 vsinα+sin(α+2π/n)+sin(α+2π*2/n)+sin(α+2π*3/n)+……+sin[α+2π*(n-1)/n]=0
8 X6 ~$ `/ ]) P: K- ^* Y* scosα+cos(α+2π/n)+cos(α+2π*2/n)+cos(α+2π*3/n)+……+cos[α+2π*(n-1)/n]=0 以及
. G9 v4 o8 |/ ?9 {0 m' w( vsin^2(α)+sin^2(α-2π/3)+sin^2(α+2π/3)=3/2
2 ^3 m" l9 Y: j! \& k/ stanAtanBtan(A+B)+tanA+tanB-tan(A+B)=0
0 \; J" N0 F; Q6 F5 j4 @2 |7 b( `3 Rcosx+cos2x+...+cosnx= [sin(n+1)x+sinnx-sinx]/2sinx |